Gathering Stones: The Problems of Modern Cultural and Activity Research - Reed M., (Культурно-историческая психология, 2017)
Cultural-Historical Psychology 2017. Vol. 13, no. 1, 4–22 doi:10.17759/chp.2017130101 ISSN: 1816-5435 / 2224-8935 (online)